Determinants of Digital Accounting Software Adoption Among Accounting Students: An Empirical Investigation Using the UTAUT - Prawita, Audithya; Maulana, Agus (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
The implementation of digital accounting software based on cloud accounting is increasing globally, including in Indonesia. Therefore, accounting students, as future professional accountants, must be highly proficient in operating digital accounting software. Despite the growing prevalence of digital tools, students’ readiness to embrace digital accounting software remains uncertain. This study aims to examine the factors influencing student’s acceptance of digital accounting software. The research was conducted on 147 accounting students from five major islands in Indonesia using a quantitative approach, analyzed through SmartPLS 3.0. The findings indicate that the primary factors influencing student’s adoption of digital accounting software are performance expectancy, social influence, and facilitating conditions. In contrast, effort expectancy does not significantly impact accounting student’s acceptance of digital accounting software. This research offers valuable insights for universities to optimize the integration of digital accounting software into their curriculum by addressing key factors such as performance expectancy, social influence, and facilitating conditions that significantly influence student adoption.